Vous êtes sur la page 1sur 4

# 29

Figure

= b3h/4

= bh /12

= b3h/12

= bh3/12

[ (
2

)]

)] 36

]3

## CIV 1201 "A"

a b sincos 6

2 2

I y = ab sin(b + a cos)

yc = (a sin )/2

Ix

I yc

I xc = a 3b sin 3 12

(
)
= [ab sin(b + a cos )] 12
= (a b sin ) 3

h 3 a 2 + 4ab + b 2
36(a + b )
3
h (3a + b )
Ix =
12

I xc =

xc = (b + a cos )/2

A = ab sin

A = h(a + b ) 2
h(2a + b )
yc =
3(a + b )

) 18
)

rx2
ry2

= (b + a cos) 3
(ab cos) 6

= (a sin) 3

ry2c = b 2 + a 2 cos 2 12

rx2c = (a sin) 12

h 2 a 2 + 4ab + b 2
18(a + b )
2
h (3a + b )
rx2 =
6(a + b )
rx2c =

rp2 = b 2 + h 2 12

J = bh b 2 + h 2 12

[ (

rx2 = h 2 3
ry2 = b 2 3

I x = bh 3 3
I y = b 3h 3

xc = b/2

ry2c = b 2 12

yc = h/2

=h 6
= b 2 + ab + a 2 6

I yc = b 3 h 12

)]

= b ab + a

A = bh

ry2c
rx2
ry2

rx2c = h 2 18

= Abh 4 = b 2 h 2 4

I xc yc = a 3b sin 2 cos 12

I xy

= bh 2 (2a + b ) 24

I xc yc = 0

I xy

= bh 2 (2a b ) 72
= [Ah(2a + b )] 12

I xc yc = [Ah(2a b )] 36

= Abh 12 = b 2 h 2 24
I xy

rx2 = h 2 6
ry2 = b 2 6

= Abh 4 = b 2 h 2 8

I xc yc = Abh 36 = b 2 h 2 72

I xy

I xc yc = Abh 36 = b 2 h 2 72

Product of Inertia

ry2c = b 2 18

rx2c = h 2 18

rx2c = h 2 12

[ (

I x = bh 12
I y = bh b 2 + ab + a 2 12

I yc = bh b ab + a

I xc = bh 3 36

Iy

Ix

I yc = b 3h/36

I x c = bh 3 /36

Iy

Ix

rx2 = h 2 6
ry2 = b 2 2

ry2c = b 2 18

I yc = b 3h/36
3

rx2c = h 2 18

I x c = bh 3 /36

I xc = b h 3 12

yc = h/3

xc = (a + b)/3

A = bh/2

yc = h/3

xc = b/3

A = bh/2

yc = h/3

xc = 2b/3

A = bh/2

30

2a

Figure

sin 2

A = a2

2

2a
sin 3
xc =
3 sincos
yc = 0

A = a 2
2a sin
xc =
3
yc = 0

A = a2/2
xc = a
yc = 4a/(3)

A = (a2 b2)
xc = a
yc = a

A = a
xc = a
yc = a

Aa 2
4

2sin 3 cos
1

3 3sin cos
2sin 3 cos
Aa 2
Iy =
1 +

4 sin cos
Ix =

## Ix = a4( sin cos )/4

Iy = a4( + sin cos )/4

I x = a 4 8
I y = 5a 4 8

I yc

a 4 9 2 64
72
= a 4 8

I xc =

5a
b
a 2 b 2
4
4
J = a4 b4 2

Ix = I y =

I xc = I yc = a 4 b 4 4

J = a 4 2

I x = I y = 5a 4 4

I xc = I yc = a 4

## Area Moment of Inertia

=a 2

)
+b ) 4

ry2 =
2

a2
4

2sin 3 cos
1

3 3sin cos
2sin 3 cos
a2
ry2 =
1 +

4 sin cos
rx2 =

a 2 ( sin cos)
4

a 2 ( + sin cos )
2
ry =
4

rx2 =

ry2 = 5a 2 4

rx2 = a 2 4

a 2 9 2 64
36 2
ry2c = a 2 4

= a + b2 2

rx2c =

rx2
rp2

(
(5a

= ry2c = a 2
= ry2 = 5a 2
2

rx2c = ry2c = a 2 + b 2 4

rx2c
rx2
rp2

I xc yc = 0
I xy = 0

I xc yc = 0
I xy = 0

I xy = 2a 2 3

I xc y c = 0

= a 2 a 2 b 2

I xy = Aa 2

I xc yc = 0

I xy = Aa 2

I xc y c = 0

Product of Inertia

31

y = (h/b1/n)x1/n

y = (h/bn)xn

Figure

xc = 3a/5

## CIV 1201 "A"

n
bh
n +1
n +1
b
xc =
2n + 1
n +1
yc =
h
2(n + 2)
A=

A = bh (n + 1)
n +1
xc =
b
n+2
h n +1
yc =
2 2n + 1

yc = 3b/8

xc = 3a/5

A = 2ab/3

yc = 0

n
bh 3
3(n + 3)
n
Iy =
b3h
3n + 1
Ix =

bh 3
3(3n + 1)
hb 3
Iy =
n+3

Ix =

Iy = 2ab3/7

Ix = 2ab3/15

I y = 4 a 3b 7

I yc = 16a b 175

I xc = I x = 4ab 3 15

A = 4ab/3

## Area & Centroid

= 3a 2 7

= 12a 175

n +1 2
h
3(n + 1)
n +1 2
ry2 =
b
3n + 1
rx2 =

h 2 (n + 1)
3(3n + 1)
n +1 2
ry2 =
b
n+3
rx2 =

rx2 = b 2 5
ry2 = 3a 2 7

ry2c
ry2

rx2c = rx2 = b 2 5

Ixy = Aab/4 =

I xc yc = 0
I xy = 0

a2b2

Product of Inertia

32

R1

R2

Figure

4 3
R
3

= mass/vol.

yc = 0
zc = 0

xc = 0

M =

M = R12 R22 h
xc = 0
yc = h 2
zc = 0
= mass vol.

= mass/vol.

## CIV 1201 "A"

(
(

= 3R

ry2
2

= 3R 2

(3R

2
1

R22

rz2c

= r 2z =

2R 5

ry2c = ry2 = 2 R 2 5
I zc = I z = 2 MR 5

)2

=
= 3R12 + 3R22 + 4h 2 12

ry2
rz2

I yc = I y = 2MR 2 5

ry2c
rx2

rx2c = rx2 = 2 R 2 5
2

+ 4h 2 12

R 2

(
= (R

= ry2 =
= rz2 =

## rx2c = rz2c = 3R12 + 3R22 + h 2 12

ry2c
rx2

rx2c = rz2c = 3R 2 + h 2 12

rx2
rz2

I xc = I x = 2MR 2 5

= M 3R12 + 3R22 + h 2 12
I y c = I y = M R12 + R22 2
Ix = Iz
= M 3R12 + 3R22 + 4h 2 12

I xc = I z c

I x = I z = M 3R 2 + 4h 2 12

zc = 0

I yc = I y = MR 2

I xc = I zc = M 3R 2 + h 2 12

I z = 3MR

I x = I y = 3MR 2

r22c = R 2

I zc = MR 2

ry2 = rz2 = L2 3

I y = I z = ML2 3

rx2c = ry2c = R 2 2

ry2c = rz2c = L2 12

I yc = I zc = ML2 12

I xc = I yc = MR 2 2

rx2 = rx2c = 0

I x = I xc = 0

## Mass Moment of Inertia

yc = h/2

xc = 0

M = R2h

=
=
=
=
=

2RA
R = mean radius
R = mean radius
0
cross-sectional area of
ring
= mass/vol.

M
xc
yc
zc
A

= LA
= L/2
=0
=0
= cross-sectional area of
rod
= mass/vol.

M
xc
yc
zc
A

## Mass & Centroid

I xc yc , etc. = 0

I xc yc , etc. = 0
I xy ,etc. = 0

I xc yc , etc. = 0
I xy , etc. = 0

I zc zc = MR 2
I xz = I yz = 0

I xc yc , etc. = 0

I xc yc , etc. = 0
I xy , etc. = 0

Product of Inertia